POLYSEMY ANALYSIS OF KATY PERRY’S SONGS: A SEMANTIC STUDY - Elihu Jemal Suryono; Afrianto Afrianto (Linguistics and Literature Students' Journal, 2023)
This study focuses on a polysemy Analysis on Perry’s Song Lyrics. To do the analysis, this study occupies semantics. Accordingly, the objectives of this study are to figure out and describe the regular polysemy and irregular polysemy found in the lyrics of Katy Perry’s songs. Figuring out the detail polysemy, this study employs qualitative descriptive method. Furthermore, to get the required data, this study uses library research. The data are in the form of words selected from the lyrics. However, to figure out the polysemy, this study still brings complete sentences which from the words taken.Keywords: Irregular polysemy, Katy Perry, polysemy, regular polysemy, semantic